Complications Following Temporary Bilateral Internal Iliac Artery Ligation for Pelvic Hemorrhage Control in Trauma. Issue 10 (October 2022) - Schellenberg, Morgan; Gallegos, Hannah; Owattanapanich, Natthida; Wong, Monica D.; Bardes, James M.; Joos, Emilie; Vogt, Kelly N.; Inaba, Kenji
Background: Temporary bilateral internal iliac artery ligation (TBIIAL) is an option for surgical control of pelvic hemorrhage after trauma. Concerns persist that complications, particularly gluteal necrosis, following TBIIAL should preclude its use, despite a lack of formal research on TBIIAL complications. This study aimed to define complications following TBIIAL for emergent control of traumatic pelvic bleeding. Study Design: Patients undergoing TBIIAL after blunt trauma (2008-2020) at our level 1 trauma center were included without exclusions. Demographics, clinical/injury data, and outcomes were collected. Descriptive statistics summarized study variables. Multivariable analysis of factors independently associated with mortality after TBIIAL was performed. Results: In total, 77 patients undergoing emergent TBIIAL after blunt trauma were identified. Median age was 46 [IQR 29-63] years. Most patients ( n = 70, 91%) were severely injured (ISS ≥16), with 43% undergoing resuscitative thoracotomy prior to TBIIAL. No local complications (gluteal necrosis, iatrogenic injury, fascial dehiscence, surgical site infection) after TBIIAL occurred over the 13-year study period. In the first 28 days after injury, median hospital-, ICU-, and ventilator-free days were 0. Mortality was 70% ( n = 54). On multivariable analysis, older age was the only variable independently associated with in-hospital mortality (OR 1.081, P = .028). Conclusion: Zero cases of gluteal necrosis, iatrogenic injury to surrounding structures, or surgical site infection/fascial dehiscence of the exploratory laparotomy occurred over the study period. High concern for gluteal necrosis after TBIIAL in severely injured trauma patients is unfounded and should not prevent a surgeon from obtaining prompt pelvic hemorrhage control with this technique among patients in extremis.